IMPROVING SIMPLE INTERRUPTED SUTURES SKILLS WITH HOME ASSIGNMENT FOR MEDICAL STUDENTS - Nicko Rachmanio; Sagiran Sagiran; Indira Rifki Amalia (Publikasi Indonesia, 2023)
The limited-time to practice during practicum becomes a problem for students to have a good surgical skill. The home assignment of performing sutures, such as a simple interrupted sutures technique is expected to be a solution. A quasi-experimental study was carried out on a sample of 20 students, divided into two groups. Group A, consisting of 10 students, received a tutorial of a simple interrupted sutures technique and was given the assignment to do the sutures at home every day and the supervisor would check their assignment the next day, for seven days. Group B, consisting of 10 other students, only received a tutorial of a simple interrupted sutures technique with the opportunity to practice independently during practicum at skills laboratory. After one week, an assessment was made based on the time it takes for each student to make a simple interrupted sutures technique. The data were analyzed with an independent T-test. There were significant differences between pre and post practices in time consumed during suturing in group A (p<0,05). The average time for group A was 533 seconds on the first day and 335 seconds after the home assignment in a week. The average time for group B was 493 seconds on the first day and 450 seconds on evaluation day. There were no significant differences in group B (p>0,05). Home assignments could improve the speed of sutures skills. The home assignment effectively improves sutures skills for medical students, especially for the limited time of practicum conditions at skills laboratories